The Maqasidian features in the ’governance according to custom’ rule - Shammam, Albasher Mohamed (Journal of Islamic Sciences, 2020)
This research deals with the correlation between the rule of custom and the purposes of Sharia, in order to enhance the understanding of the purposes of legislation in what is considered normative. The researcher adopted the inductive, analytical and descriptive approach, and through this he reached the following conclusions: • A close link exists between the rules of jurisprudence and the purposes of Sharia. • The rule of “custom is tight” is used for determining uncontrolled matters. • The recognition of people’s norms and practices pertains to the flexibility of the glorious Sharia law. • Referral to norms is not absolute, but rather the flexible aspect of legislation.